2021
DOI: 10.7554/elife.54346
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between germ cell-less and Torso receptor regulates transcriptional quiescence underlying germline/soma distinction

Abstract: Transcriptional quiescence, an evolutionarily conserved trait, distinguishes the embryonic primordial germ cells (PGCs) from their somatic neighbors. In Drosophila melanogaster, PGCs from embryos maternally compromised for germ cell-less (gcl) misexpress somatic genes, possibly resulting in PGC loss. Recent studies documented a requirement for Gcl during proteolytic degradation of the terminal patterning determinant, Torso receptor. Here we demonstrate that the somatic determinant of female fate, Sex-lethal (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Instead, they spread into the posterior region of the embryo and are found associated with somatic nuclei. A similar disruption in the proper distribution of pole plasm during PGC cellularization was found when the terminal pathway was upregulated by blocking degradation of Torso, or by a constitutive allele of the downstream MEK kinase [12]. Moreover, as shown here, we find that Vasa is lost from PGCs when the terminal pathway is optogenetically activated at the posterior of the embryo.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Instead, they spread into the posterior region of the embryo and are found associated with somatic nuclei. A similar disruption in the proper distribution of pole plasm during PGC cellularization was found when the terminal pathway was upregulated by blocking degradation of Torso, or by a constitutive allele of the downstream MEK kinase [12]. Moreover, as shown here, we find that Vasa is lost from PGCs when the terminal pathway is optogenetically activated at the posterior of the embryo.…”
Section: Discussionsupporting
confidence: 85%
“…Studies by Pae et al (2017) [65] showed that Gcl targets the terminal pathway receptor Torso for proteolytic degradation, thereby shutting down the pathway at the very posterior pole of the embryo. When the terminal signaling cascade is activated at the posterior pole, either in gcl mutants or by gain-of-function mutations in the Torso receptor or its downstream kinases, pole plasm components are not properly incorporated into PGCs when they cellularize [12]. These observations raise the possibility that the BMP pathway might be needed to help suppress the terminal signaling pathway.…”
Section: Bmp Signaling Is Required To Suppress the Functioning Of The Terminal Pathwaymentioning
confidence: 99%
See 3 more Smart Citations